IMPROVING STUDENTS’ WRITING ABILITY AND MOTIVATION USING COOPERATIVE AND COLLABORATIVE LEARNING IN TEACHING WRITING TO ENGLISH DEPARTMENT STUDENTS OF UNIVERSITAS PAMULANG - Sariasih, Wiwit - (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2019)
ABSTRACT This research was conducted to increase students' writing ability and motivation using cooperative and collaborative learning. It was aimed to reveal; 1) To what extent cooperative and collaborative learning can improve students’ writing ability? 2) How is students’ motivation in writing lesson after implementing the cooperative and collaborative learning? 3) What are factors that influence the improvement of ability and motivation of students in writing? The research was conducted using classroom action research design and the data were divided into qualitative and quantitative data. Qualitative data were taken from observation, questionnaire and interview while quantitative data were taken from writing assignment and test. Thus, it was found that students’ writing ability and motivation was increased after using cooperative and collaborative learning. The factors that influenced the improvement were classroom activities, classroom management and lecturer’s strategy in teaching. Keywords: Cooperative and Collaborative Learning, Motivation and Writing